If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4 + u)(4u + 6) = 0 Reorder the terms: (4 + u)(6 + 4u) = 0 Multiply (4 + u) * (6 + 4u) (4(6 + 4u) + u(6 + 4u)) = 0 ((6 * 4 + 4u * 4) + u(6 + 4u)) = 0 ((24 + 16u) + u(6 + 4u)) = 0 (24 + 16u + (6 * u + 4u * u)) = 0 (24 + 16u + (6u + 4u2)) = 0 Combine like terms: 16u + 6u = 22u (24 + 22u + 4u2) = 0 Solving 24 + 22u + 4u2 = 0 Solving for variable 'u'. Factor out the Greatest Common Factor (GCF), '2'. 2(12 + 11u + 2u2) = 0 Factor a trinomial. 2((4 + u)(3 + 2u)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(4 + u)' equal to zero and attempt to solve: Simplifying 4 + u = 0 Solving 4 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + u = 0 + -4 Combine like terms: 4 + -4 = 0 0 + u = 0 + -4 u = 0 + -4 Combine like terms: 0 + -4 = -4 u = -4 Simplifying u = -4Subproblem 2
Set the factor '(3 + 2u)' equal to zero and attempt to solve: Simplifying 3 + 2u = 0 Solving 3 + 2u = 0 Move all terms containing u to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2u = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2u = 0 + -3 2u = 0 + -3 Combine like terms: 0 + -3 = -3 2u = -3 Divide each side by '2'. u = -1.5 Simplifying u = -1.5Solution
u = {-4, -1.5}
| (z+2)(z+9)=0 | | 7y+23=-3y | | (z+2)(z-9)=0 | | -4+4(3x-8)=6x-30 | | 14m-(2m+8)=0 | | -14z-4(2-5z)=-29 | | 4x+8y=180 | | -2(k+6)=-5 | | (2x-9)*2+(3x-14)*2=(x-1)*2 | | f(-2)=-8a+44-2b+4 | | -4(5x+7)= | | 164=8h+4h+50 | | 17-2x=8x-35 | | -(-4+6p)+3(7+4p)= | | a*a-1=x | | 4a+2a-a= | | 60b-b=96 | | -6=5d-9 | | 12*b*b*b*4*b*b*b=x | | x^8-x^7+12x^2-84+41x-71x^3=0 | | 7y-6y= | | 2x^2+22x+121=0 | | 3c^2-9c-6=0 | | 3c^2+9c-6=0 | | (5u-5v)(7u-6v)= | | -4(t-2)+7t=5t-6 | | (5u-5v)x(7u-6v)= | | 7-5x=12-10x | | (x+25)(x+10)=1000 | | 2x=5(1) | | (x+2)*(x+2)=x*x+6 | | 54x+42=158 |